2014
DOI: 10.1103/physrevlett.113.027205
|View full text |Cite
|
Sign up to set email alerts
|

Pinning-Dependent Field-Driven Domain Wall Dynamics and Thermal Scaling in an UltrathinPt/Co/PtMagnetic Film

Abstract: Magnetic-field-driven domain wall motion in an ultrathin Pt/Co(0.45  nm)/Pt ferromagnetic film with perpendicular anisotropy is studied over a wide temperature range. Three different pinning dependent dynamical regimes are clearly identified: the creep, the thermally assisted flux flow, and the depinning, as well as their corresponding crossovers. The wall elastic energy and microscopic parameters characterizing the pinning are determined. Both the extracted thermal rounding exponent at the depinning transitio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 37 publications
9
117
0
Order By: Relevance
“…An alternative homogeneous explanation attributes the secondary relaxation phenomena to small-angle reorientations of all molecules 12,46,47 . In our previous work on CCl 4 48 we found that the monoclinic phase of this compound has essentially the same dynamical behavior, as function of temperature, as that of its isostructural glass formers, CBrCl 3 and CBr 2 Cl 2 . The simulations clearly show that there are preferential axes of rotation, which are fixed with respect to the crystal orientation.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…An alternative homogeneous explanation attributes the secondary relaxation phenomena to small-angle reorientations of all molecules 12,46,47 . In our previous work on CCl 4 48 we found that the monoclinic phase of this compound has essentially the same dynamical behavior, as function of temperature, as that of its isostructural glass formers, CBrCl 3 and CBr 2 Cl 2 . The simulations clearly show that there are preferential axes of rotation, which are fixed with respect to the crystal orientation.…”
Section: Introductionmentioning
confidence: 74%
“…The jumps for all molecules were detected using a running test algorithm based on a signal to noise measure described in our previous work for CCl 4 48 . After analyzing the trajectories for the N =512 molecules in the system, the times t n,i at which every single jump occurs were registered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of temperature in the flow (3) cures this nonanalyticity rounding the singularity (cusp in the function ). For d > 2 the cusp around the origin in presence of temperature appears asymptotically at large scales for which the temperature renormalizes to zero according to (3). The fixed point solution for RP systems for u ∈ [0,1] is known exactly and reads [19,28]:…”
Section: Functional Rg Approachmentioning
confidence: 99%
“…Typically these are divided into two categories. One encompasses interfaces in magnetic [2,3], ferroelectric [4,5] materials or spintronic systems [6], fluid invasion in porous media [7] and fractures [8,9]. The second concerns random periodic systems such as charge-density waves [10], vortex lattices in type II superconductors [11] and Wigner crystals [12].…”
Section: Introductionmentioning
confidence: 99%